Processo de trabalho do Ministério Público em defesa da saúde: quando “novos” atores entram em cena - Souza, Kleize Araújo de Oliveira (2009)
Study about work process of Public Ministry (MP) in the city of Feira de Santana - BA. Our objectives were analyze the MP work process in defense of the citizens health right in Feira de Santana-BA city and describe the users complaint and/or denunciation(s) that search the health right. Its theoretic referential understood the social movements and social control in Brazilian health, the Public Ministry institutionalization in health defense and the work process of this institution in defense of the individual and collective health. Qualitative research, in a critical and analytical perspective -, having as inquiry field the Public Ministry of Feira de Santana – BA. The participant subjects of the study had been divided in three groups: Group I, justice promoter (three); Group II, users looking for the MP to defend its interests and health rights (nine); and Group III, Secretaria Municipal de Saúde representatives (two). The techniques of data production had been systematic comment, half-structuralized interview and document analysis. To analyze the data, we found an approach to Hermeneutics-dialectic method, from which were elaborated two analysis categories: Category 1 - Public Ministry: social rights guard versus board salvation for laypeople, that brings an understanding for the interviewed ones about the Public Ministry; Category 2 - The daily one of Public Ministry work in health defense: techniques action no articulation versus politics action, analyses the MP work process in relationship to techniques actions, and politics actions developed for the Public Ministry in health defense of the population. The data shows that the Public Ministry actions play an important role in the democracy continuity, by the way its is not tied with public power (executive, legislative or judiciary), representing the law defender, and over all, a society protector. Thus, the MP has configured as an efficient articulator in the conflict resolution, searching to construct or no construct the difference created between the existing rights and the social reality, that is, enters the world of the right and the facts. For in such it’s necessary to give to greater transparency and visibility to the MP work process. This institution plays technical and political activities in health defense. Amongst the technical activities, that generally process through a complaint-behavior system, they are the selection, the promoter attendance for the to the user and for the use of some instrument as the Civil Inquiry, the Term of Adjustment of Behavior and the proper jurisdiction through the Public Civil action. However the extrajudicial way is preferred by the promoters. In relation to the main complaints and/or denunciations in search of the health right there are the medicine solicitation, medical error, bad treatment, administrative improbity in health institutions. In relation to the activities politics we observed that the justice promoters, when acting as society partners try to promote a citizen conscience, informing the citizen about the importance in searching its rights and duties. However, we do not perceive active participation of the Public Ministry in the construction and implementation of related health public politics, not to be the participation of the promoter of the Pole of Infancy and Youth in the formation of commissions for the infancy violence confrontation. This situation is in part, due to lack of joint between municipal council member and attorneys general of health. The found data had disclosed that the right to the health needs (reverse speed) to be constructed and to be defended collectively by managers, professionals of health, professionals of right and users with intention to assure the health as right of all and to have of the State, guaranteed in the Federal Constitution of 1988.